The Directional Case in Kalmyk (Evidence from the Epic of ‘Jangar’) - E. V. Bembeev; T. D. Mandzhieva (Oriental Studies, 2018)
The article considers the use of the directional case with evidence from multi-temporal records of the Kalmyk heroic epic of Jangar. The language of the epic - oral-poetic by nature with its certain impact in the development of the national literary language - definitely reflects the living colloquial language at the time the epic songs were recorded and, thus, preserved. The language of the epic comprises both new forms and some archaic features that stand for a certain stage of language development. The analysis of multi-temporal Jangar texts reveals that within the early records (the first half of the 19th century) the directional case formant -ur/-ür was not used. This is supported by some data on Kalmyk grammar issued at approximately the same time. However, A. Bobrovnikov points out special particles -γur; -gür (-uur; -öür in Kalmyk and colloquial Mongolian) and defines their functional-semantic meaning as ‘the one describing the path to follow or line of action’. Along with this, we have also examples of an affix etymologically similar to that of the directional case and initially found within adverbs semantically denoting the direction of motion or place. The directional case as such was first mentioned in the Grammar of Colloquial Kalmyk by V.L. Kotwicz. Records of the first half of the 20th century (the epic cycle of Eelyan Ovla, epic cycle of taleteller Mukebyun Basangov, epic cycle of taleteller Dava Shavaliev, a song from the repertory of Badma Obushinov) already contain forms of the directional case (-ur/-ür) in nominative parts of speech. Besides, the directional affix is often followed by possessive markers (-n/-n’). Of special interest is the fact that there is an adverbial suffix (-uur; -öür in Kalmyk and colloquial Mongolian) etymologically similar to that of the directional case (-ur/-ür) and semantically denoting the direction of motion or place. We may conclude that during the formation of the directional case there were two mutually approaching processes: the adverbial suffix (-uur; -öür in Kalmyk and colloquial Mongolian) semantically merged with the postposition-adverb uruγu→uru →ruu (rüü / luu / lüü) → uurр (üür) ‘downwards, towards’. Thus, it can be concluded that the directional case took its final form in colloquial Kalmyk at the turn of the 19th-20th centuries, absorbing some functions of the dative-locative and instrumental cases; it was also accompanied by decrease in the use of the postposition tal ‘towards’.